Evaluating voluntary aloneness in childhood: Initial validation of the Children’s Solitude Scale - Galanaki, Evangelia P.; Mylonas, Kostas; Vogiatzoglou, Panagiota S. (European Journal of Developmental Psychology, 2015)
This work intends to psychometrically evaluate the newly developed Children’s Solitude Scale (CSS), a measure of voluntary aloneness in childhood. The scale assesses individual differences on what children prefer to do when they want to be alone, a rather neglected, although important developmental issue. Participants were 833 fourth and sixth graders from Athens, Greece. Confirmatory factor analysis indicated four factors, although with a less-than-optimal fit: Self-Reflection, Autonomy/Privacy, Activities and Concentration. The scale showed adequate internal consistency and test-retest reliability as well as convergent and divergent validity (i.e., positive association with positive attitude towards aloneness and ability to be alone, no association with negative attitude towards aloneness, and low positive correlation with loneliness and social dissatisfaction). The results indicated the suitability of the CSS to assess reasons or motives for solitude during middle and late childhood and the necessity to further examine the structure of this type of solitude experiences in this age period.